2008
DOI: 10.1007/s00228-008-0492-8
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A induction and inhibition by different antiretroviral regimens reflected by changes in plasma 4β-hydroxycholesterol levels

Abstract: Changes in plasma 4beta-hydroxycholesterol following the initiation of efavirenz- or atazanavir/ritonavir-based antiretroviral therapy reflected the respective net increase and decrease of CYP3A activity of these regimens. The plasma 4beta-hydroxycholesterol level did not indicate a net CYP3A inhibition in the lopinavir/ritonavir arm, possibly because of concomitant enzyme induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 12 publications
10
64
0
Order By: Relevance
“…However, the use of 4b-OHC as a biomarker for decreased CYP3A4 activity by enzyme inhibition with drugs may be limited due to the long half-life of this oxysterol, requiring weeks of inhibitor administration dmd.aspetjournals.org for reductions in plasma levels to become apparent (Josephson et al, 2008). In the context of disease effects on CYP3A4 activity, our results in NAFLD, as well as those reported for Crohn's disease (Iwamoto et al, 2013), show that 4b-OHC may be a valid biomarker of reduced metabolic activity for chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of 4b-OHC as a biomarker for decreased CYP3A4 activity by enzyme inhibition with drugs may be limited due to the long half-life of this oxysterol, requiring weeks of inhibitor administration dmd.aspetjournals.org for reductions in plasma levels to become apparent (Josephson et al, 2008). In the context of disease effects on CYP3A4 activity, our results in NAFLD, as well as those reported for Crohn's disease (Iwamoto et al, 2013), show that 4b-OHC may be a valid biomarker of reduced metabolic activity for chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 4b-hydroxycholesterol was first reported to be formed solely by CYP3A4 (Bodin et al, 2001). Markedly elevated concentrations of 4b-hydroxycholesterol were found in patients treated with CYP3A4 inducers (Niemi et al, 2006;Josephson et al, 2008;Wide et al, 2008;Diczfalusy et al, 2009;Goodenough et al, 2011), and decreased concentrations have been detected in patients treated with CYP3A4 inhibitors (Josephson et al, 2008;Lütjohann et al, 2009;Goodenough et al, 2011). Furthermore, a relationship between blood 4b-hydroxycholesterol concentration and the number of active CYP3A5*1 alleles has been demonstrated, suggesting that 4b-hydroxycholesterol is not only formed by CYP3A4, but also by CYP3A5 .…”
Section: Introductionmentioning
confidence: 93%
“…8 Its plasma concentration increases in subjects treated with known CYP3A4 inducers such as carbamazepine, phenytoin, phenobarbital, rifampicin, ursodeoxycholic acid and efavirenz. 8,[30][31][32][33][34][35] It was also shown that inhibitors of CYP3A4, ritonavir and itraconazol, reduce the plasma level of 4b-hydroxycholesterol. 35,36 However, recently, TomalikScharte et al 37 reported a weak correlation between cholesterol-and midazolam-based CYP3A metrics and hence questioned the validity of 4b-hydroxycholesterol as a CYP3A biomarker.…”
Section: Cyp3a Markermentioning
confidence: 99%